Pathways to Climate Health: Active learning and effective communication to optimize climate change action an evaluation of the climate change and renal health awareness and education toolkit for healthcare providers: Reducing climate-health risks in primary care - Christie Torres; Jane Dixon (Elsevier, 2023)
Introduction: Globally, the combined effects of extreme heat due to climate change, dehydration, and socioeconomic disparities have been linked to preventable kidney disease. Health care professionals (HCPs) must elevate mitigation of climate change impacts on health by integrating climate-aware health strategies into routine practice, but there is little guidance on specifically how to do this. Methods: This quality improvement report describes the development of a climate change and renal health toolkit for HCPs, and its implementation in two primary care clinics in a Central Texas Veterans Administration medical center (United States). The toolkit was accessed by HCPs who completed pre (n=43) and post (n=33) assessments to measure their attitudes and self-efficacy in facilitating a climate-health discussion with patients on the impacts of climate change on kidney health; knowledge of climate change and kidney disease also was assessed. Results: We found significant increases in HCPs' attitudes and self-efficacy for facilitating discussion with patients on impacts of climate change on kidney health and related responsibilities in primary care, with 90% reporting improved confidence for discussing climate change and health with patients. We also found significant improvement in HCPs' knowledge about climate change and kidney disease. Discussion: Findings indicate that a self-led and easily accessible toolkit is feasible to implement, is well-received by HCPs, and achieves the established educational goals. Conclusion: This approach provides an evidence-based model for continued efforts to inform health practice for integration of climate change into clinical practice.